2020
DOI: 10.15421/012047
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular wax composition of mature leaves of species and hybrids of the genus Prunus differing in resistance to clasterosporium disease

Abstract: The interaction of a host plant with pathogen implies an extremely complex process involving the outer waxy layer of the cuticle, cutin, cell membrane, and intracellular structures. However, the initial contact between plants and pathogens takes place in cuticular waxes covering the surface of leaves, stems and fruits. Despite many findings on the role of plant epicuticular waxes, there is a gap in the understanding of the relationship between individual compounds and their functions. The pathogenic fungus Cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…‘Bluefre‘ and ‘President’ showed mid-high SHD incidences, and ‘Stanley’ showed low SHD incidences (91–100%, 62–91%, and 8.4–30%, respectively) at harvest in all years, independently of a training system ( Table 5 ). In agreement with the previous research of Benedek et al [ 30 ], Romanazzi et al [ 33 ], Bubici et al [ 7 ] and Khromykh et al [ 34 ], our results indicate that SHD resistance has a great influence on the disease’s development; therefore, the successful incorporation of the promising SHD-resistant plum cultivars into the growing practice is essential in those plum-growing areas where SHD is endemic. In addition to the SHD susceptibility of a plum’s genotype, the nitrogen and potassium content of the leaves [ 35 ] and the growth habits of the trees (e.g., a dense type of canopy or an open type of canopy) can also be factors that cause differences in the observed final SHD incidences [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…‘Bluefre‘ and ‘President’ showed mid-high SHD incidences, and ‘Stanley’ showed low SHD incidences (91–100%, 62–91%, and 8.4–30%, respectively) at harvest in all years, independently of a training system ( Table 5 ). In agreement with the previous research of Benedek et al [ 30 ], Romanazzi et al [ 33 ], Bubici et al [ 7 ] and Khromykh et al [ 34 ], our results indicate that SHD resistance has a great influence on the disease’s development; therefore, the successful incorporation of the promising SHD-resistant plum cultivars into the growing practice is essential in those plum-growing areas where SHD is endemic. In addition to the SHD susceptibility of a plum’s genotype, the nitrogen and potassium content of the leaves [ 35 ] and the growth habits of the trees (e.g., a dense type of canopy or an open type of canopy) can also be factors that cause differences in the observed final SHD incidences [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…One report suggested that hydrocarbon tetrapentacontane could positively and negatively regulate the rhizosphere microbial diversity [ 37 ]. Khromykh et al reported that tetrapentacontane is correlated with metabolic reprogramming in the epidermal cells of infected leaves of Prunus species [ 38 ]. Upon Zn and Cu treatment, 13 compounds were detected in the exudates.…”
Section: Resultsmentioning
confidence: 99%